Network disruption detected in PK (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Pakistan. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: PK-2026-0008. Severity: critical. Confidence: 70%